(untitled) (Clinics, 2008)
INTRODUCTION: The six-minute walk test (6WT) has been proposed to be a submaximal test, but could actually demand a high level of exercise intensity from the patient, expressed by a respiratory quotient >;1.0, following the guideline recommendations. Standardizing the 6WT using the Borg scale was proposed to make sure that all patients undergo a submaximal walking test. PURPOSE: To test the reproducibility of the six-minute treadmill cardiopulmonary walk test (6CWT) using the Borg scale and to make sure that all patients undergo a submaximal test. METHODS: Twenty-three male heart failure patients (50±9 years) were included; these patients had both ischemic (5) and non-ischemic (18) heart failure with a left ventricle ejection fraction of 23±7%, were diagnosed as functional class NYHA II-III and were undergoing optimized drug therapy. Patients were guided to walk at a pace between "relatively easy and slightly tiring" (11 and 13 on Borg scale). The 6CWT using the Borg scale was performed two times on a treadmill with zero inclination and patient control of speed with an interval of 24 hours. During the sixth minute, we analyzed ventilation (VE, L/min), respiratory quotient, Oxygen consumption (VO2, ml/kg/min), VE/VCO2 slope, heart rate (HR, bpm), systolic blood pressure (SBP, mmHg), diastolic (DBP, mmHg) blood pressure and distance. RESULTS: The intraclass correlation coefficients at the sixth minute were: HR (r i=0.96, p